Human Mobility Response to Natural Disasters and Environmental Change - Manawadu, L.; Wijeratne, V.P.I.S. (Springer, 2022)
Being a tropical country, Sri Lanka experiences many vulnerable natural disasters induced by climatic change causing direct repercussions on basic living standards of the population. A significant proportion of the population of Sri Lanka is suffering from negative impacts of natural disasters. This study mainly focuses on the nature of human mobility responses and human migration responses to natural disasters in Sri Lanka and finally the consequences and human adaptations for disaster-induced human mobility. The study used secondary data, semi-structured interviews, as well as related literature to achieve the intended objectives. Results revealed that Sri Lanka is wrecked by a series of droughts, floods, and landslides every year enforcing government to a huge budgeting on risk reduction and disaster management. According to the statistics provided by the Disaster Management Center, half a million people and about 100,000 people had been displaced in 2017 and 2018, respectively, due to natural disasters in Sri Lanka. Tsunami, which took place in 2004, displaced more than 450,000 people, recording it as the most vulnerable natural disaster in Sri Lanka. The 2004 tsunami has forced people to move away from their original residences. Disaster-induced displacements have become a big conflict between communities at present due to their competition for natural resources and opportunities in the new environment. Therefore, livelihood recovery and human adaptations have become a serious issue in disaster-induced migrations in Sri Lanka, owing to limited socioeconomic facilities in the new environment. Although the succeeded governments have attempted to introduce new policies and guidelines, still Sri Lanka has no proper policy to address the needs of people displaced by disasters. Therefore, more emphasis should be given on the policies and actions related to climate-induced migration to enhance the resilience.
Keywords: Human mobility; Natural disasters; Climate change; Displacement